2022
DOI: 10.32604/csse.2022.019938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Vulnerabilities on Cybersecurity

Abstract: Today, security is a major challenge linked with computer network companies that cannot defend against cyber-attacks. Numerous vulnerable factors increase security risks and cyber-attacks, including viruses, the internet, communications, and hackers. Internets of Things (IoT) devices are more effective, and the number of devices connected to the internet is constantly increasing, and governments and businesses are also using these technologies to perform business activities effectively. However, the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…With 80-85% of successful cyber-attacks (malware, ransomware, phishing, etc.) occurring due to human error, there is still a lot to do in terms of securing the wide attack surface [33]. Deploying secure, vigilant, and resilient data needs must be established, for providing a digital footprint (real-time insights and visibility of the productions' cyber threat surface) when where intelligent devices are employed in the environment.…”
Section: Data Security It/ot Cybersecurity Standards and Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…With 80-85% of successful cyber-attacks (malware, ransomware, phishing, etc.) occurring due to human error, there is still a lot to do in terms of securing the wide attack surface [33]. Deploying secure, vigilant, and resilient data needs must be established, for providing a digital footprint (real-time insights and visibility of the productions' cyber threat surface) when where intelligent devices are employed in the environment.…”
Section: Data Security It/ot Cybersecurity Standards and Risk Assessmentmentioning
confidence: 99%
“…Deploying secure, vigilant, and resilient data needs must be established, for providing a digital footprint (real-time insights and visibility of the productions' cyber threat surface) when where intelligent devices are employed in the environment. Applying the same level of security for all devices will allow quick detection of malicious nodes/devices [24,25,26,27,28,29,30,31,32,33], however, this strategy may not be workable in scenarios where certain types of devices have higher priority of security than the rest (e.g., maritime facilities, nuclear). Manufacturing sectors are progressively implementing security standards, controls, multi-factor authentication, and Zero Trust (ZT) [34] models for both their IT/OT and cloud domains.…”
Section: Data Security It/ot Cybersecurity Standards and Risk Assessmentmentioning
confidence: 99%
“…Firstly, the lack of awareness is a significant issue; many organizations and individuals still lack adequate cybersecurity awareness, making it easier for attackers to succeed. Information security awareness gives the user more understanding of the importance of the best practices [5] .A study conducted by [6] in Saudi Arabia, involving participants from all regions, showed that the general findings indicate a low level of awareness concerning cybersecurity and information security, with only 61% awareness achieved. The result emphasizes the importance of raising awareness to its maximum potential.…”
Section: Problem Statement and Significancementioning
confidence: 99%
“…These methods within the cybersecurity domain are on the verge of becoming outdated. Sandboxes, antivirus controls, secure email, and other standard technologies were designed to protect networks from direct attackers [6]. To deal with the new phishing assaults that target vulnerable employees, new teaching methods are required [7].…”
Section: Problem Statement and Significancementioning
confidence: 99%
“…Para prevenir los ciberataques o, al menos, protegerse ante ellos, las grandes corporaciones están invirtiendo incontables cantidades de dinero en la mejora de los departamentos de ciberseguridad haciéndolos cada vez más grandes con la contratación de profesionales especializados en dicho ámbito [3,99]. El objetivo que se persigue es el de evitar la pérdida y exfiltración de datos, mantener la reputación y, probablemente, su mayor preocupación, minimizar en todo lo posible el impacto en la continuidad del negocio [9,171].…”
Section: Introductionunclassified